Credit Relaxation as an Instrument of Legal Protection for Debtors During the Covid-19 Pandemic - Edison; Rr. Ani Wijayati; Diana Ria Winanti Napitupulu (Leges Privatae, 2025)
This article is structured based on research conducted on the case of PT. Pasundan Jaya. The fundamental points used as the foundation or the main topic of this study involve examining the legal protection mechanisms for debtors unable to fulfil their obligations in the future, the obstacles faced in acquiring legal protection due to their incapacity, and the legal efforts made by debtors to address these obstacles, particularly during the Covid-19 pandemic. This research employs a qualitative methodology with a normative juridical approach guided by the perspectives of Soerjono Soekanto and Sri Mamudji. It is descriptive-analytical and empirical, involving observations and interviews with several sources. The research findings encompass restructuring or relaxation of credit involving changes in credit agreements such as interest rates, timeframes, or payments; The credit restructuring policy applies to banking and financing until March 2023 due to the Covid-19 pandemic; Presidential Decree No. 12 of 2020 acknowledges unforeseen events regulated by law, stating that defaulting due to Covid-19 is not a breach of contract; and The Covid-19 pandemic is deemed as force majeure, among other aspects